The Influence of Husband's Support on Mother's Readiness for the Labor Process at TPMB Ny. Afita Delianah, Turen, Malang - Anik Purwati; Retno Dewi Prisusanti; Maria Veronika Widiatrilupi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Every pregnant woman requires proper care throughout her pregnancy, as it is a critical time for both the mother and the developing fetus. However, many husbands tend to leave their wives to cope on their own, especially after childbirth, not fully realizing the emotional and psychological challenges their wives face. Pregnancy often brings anxiety and fear, and during this time, a pregnant woman greatly needs support from her husband, family, and others around her. The husband’s reactions and behaviors, along with his attitude towards the pregnancy and childbirth, can significantly influence the mother’s emotional and psychological readiness for labor. A supportive husband can help reduce anxiety and increase the mother’s confidence and preparedness for the labor process. This study aims to examine the relationship between husband’s support and the mother’s readiness in facing the labor process. The research design used for this study is correlational, which aims to identify the relationship between variables. The sample for this study consisted of pregnant women attending TPMB Ny. Afita Delianah in Turen Subdistrict, Malang Regency. Data was collected through a structured questionnaire, and statistical analysis was performed using the Chi-Square test. The results of the study indicated a significant relationship between husband’s support and the mother’s readiness for labor, with a p-value of 0.001 (p < 0.05). This finding underscores the importance of involving husbands in the pregnancy and labor process, as their emotional and practical support can have a profound impact on the mother’s mental and emotional state. It is essential that healthcare professionals and family members encourage and provide opportunities for husbands to actively support their wives during this critical time, as it can positively affect the overall childbirth experience